Drug scene in the Czech Republic and Slovakia during the period of transformation - Csémy, Ladislav; Kubicka, Ludek; Nociar, Alojz (European addiction research, 2002)
The article describes the development of drug-related problems in the context of the rapid sociopolitical and economic changes in the Czech Republic and the Slovak Republic. The period of the last decade is marked by an increase in drug use in both countries; 17% of adults in the Czech Republic and 12% of the Slovaks report lifetime drug use. The respective figures are even higher for the population of adolescents. According to the data from the ESPAD survey carried out in 1999, 35% of young Czechs and 19% of young Slovaks used marijuana. Metamphetamine is the most misused substance among problem drug users in the Czech Republic, and heroin dominates in Slovakia. The response of the society to social and health problems caused by drugs is discussed in the following areas: institutional differentiation, political coordination and legislative development. The need for further social research is stressed.
Keywords: methamfetamin; Crime; Methamphetamine; heroin; Adolescent; Slovakia; Social Change; lidé; politika; Heroin; hospitalizace; sociální změna; Czech Republic; Hospitalization; Socioeconomic Factors; Politics; Česká republika; Substance-Related Disorders; Slovenská republika; socioekonomické faktory; poruchy spojené s užíváním psychoaktivních látek; zločin; mladiství; Humans